Factores asociados al incumplimiento terapéutico en pacientes hipertensos - Ayala Ayala, Miriam Elizabeth (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
Arterial Hypertension is the second most common cause of consultation in the primary level of medical care, since the IMSS is the public institution that provides attention to most of this population. Only 19.4% of the hypertensive patients are controlled. Recent studies have established that there are many factors associated with uncontrolled blood pressure in hypertensive patients. OBJECTIVES: To identify the related factors to poor treatment adherence in uncontrolled hypertensive patients of the UMF 80. MATERIALS AND METHODS: Observational, descriptive, retrospective and cross-sectional study. We included female and male patients, from 20 to 65 years old, 1 to 10 years of diagnosis. Neurologic, psychiatric and end stage renal disfunction patients were excluded.123 patients were randomly collected and to whom we applied the Brief Medication Questionnaire. We measured their blood pressure, body mass index and abdominal circumference. Laboratory studies were collected from the medical files. RESULTS: We studied 63.4% women and 36.6% men. 90% of the population was of medium adulthood age. 52% of women and 30.1% of men were non-adherent. 22% of hypertensive patients were uncontrolled. 77% of the obese/overweight patients were non-adherent. About 72.4% of non-adherent patients had abdominal circumference greater than the recommended. 51.2% of the non-adherent patients had hypertriglyceridemia. The percentage of patients who were also diabetic was similar between the adherent and non-adherent group. Only the non-adherent patients reported secondary effects and medication aversion. CONCLUSIONS: 22% of the patients had uncontrolled hypertension. Factors such as female gender, abnormal body mass index and abnormal waist-to-hip index, evolution time of the disease, concomitant uncontrolled Diabetes, high triglycerides, multi-dose hypertensive drugs and beliefs about medication are associated to poor treatment adherence.

La HAS es el segundo motivo de consulta en el primer nivel de atención médica, siendo el IMSS la institución pública que mayor número de población mexicana hipertensa atiende. Sólo el 19.4% de los pacientes hipertensos se encuentran controlados. Existen numerosos factores asociados al descontrol del paciente hipertenso. OBJETIVOS: Identificar los factores relacionados con la falta de adherencia al tratamiento en pacientes hipertensos descontrolados de la UMF80. MATERIALES Y MÉTODOS: Estudio descriptivo, observacional, transversal y retrospectivo. Se incluyeron pacientes de ambos sexos, de 20 a 65 años de edad, con 1 a 10 años de diagnóstico. Se excluyeron los pacientes con enfermedades neurológicas o psiquiátricas y con ERC estadio V. A 123 pacientes recolectados al azar se les aplicó el Cuestionario Breve de Medicación, se les tomó TA, IMC y circunferencia abdominal. Los estudios de laboratorio se recabaron del expediente clínico. RESULTADOS: Se estudiaron 63.4% de mujeres y 36.6% de hombres. El 90% de la población fue de edad adulta media. El incumplimiento se presentó en el 52% de mujeres y 30.1% de hombres. El 22% de los pacientes tenían HAS descontrolada. De los pacientes con sobrepeso y obesidad, 77% fueron incumplidores. 72.4% de los pacientes incumplidores tenían circunferencia abdominal mayor a lo recomendable. El 51.2% de los pacientes incumplidores presentaban hipertrigliceridemia. El porcentaje de pacientes con DM2 fue similar entre cumplidores y no cumplidores. Solamente los pacientes incumplidores reportaron aversión a la medicación y efectos secundarios. CONCLUSIONES: Los factores relacionados con falta de adherencia fueron edad mayor a 41 años, sobrepeso u obesidad, circunferencia abdominal mayor a lo recomendable, aversión a la medicación y efectos secundarios a los antihipertensivos.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4274; info:eu-repo/classification/cti/3; FCMB-E-2017-0293; Cuestionario; Incumplimiento terapéutico; Medicación